Efek Gastroprotektor Madu Terhadap Penyembuhan Tukak Lambung - Anisa Dian Pratiwi (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: One of the diseases that many people experience are gastrointestinal disorders, one of which is peptic ulcer, the excessive secretion of gastric acid (HCL) and pepsin by the gastric mucosa. The incidence of peptic ulcers is common due to Helicobacter pylori infection. Treatment and prevention of the diseases using traditional medicines are widely used, one of which is honey. Honey has general content consisting of glucose, fructose, sucrose, water, and number of amino acid, vitamins, minerals that are useful in the process of wound healing such as anti-inflammatory, antibacterial, antioxidant, and accelerate wound healing activities. Objective : To know the gastroprotective effect of honey on healing peptic ulcers. Methods : Using literature studies from national and international journals by summarizing the topic of discussion and comparing the results presented in the article. Results : Honey has gastroprotective effect with hyperosmolar characteristic due to its high concentration of sugar and low concentration of water which causes increase in osmotic pressure and water inside the microbial cells to come out so resulting in plasmolysis. Honey also has hygroscopic characteristic due to its low pH which allows microbes to dehydrate and doesn’t allow them to grow. High concentration of sugar in honey has osmotic characteristic that can inhibit bacterial growth. Conclusion: Honey has gastroprotective effect to help the healing process of peptic ulcers because it has potential as anti-inflammatory, antioxidant, antibacterial, and stimulates wound healing.